A 5-Year Survival Analysis of 160 Biomet Magnum M2 metal-on-Metal Total Hip Prostheses. Issue 1 (January 2016) - Koper, Maarten C.; Mathijssen, Nina M.C.; Vehmeijer, Stephan B.W.
Background: Large-head metal-on-metal (MoM) total hip arthroplasties (THA) are associated with high failure rates and possible pseudotumour formation. This study reports the first results of 160 Biomet Magnum M2 large-head MoM total hip articulations. Patients and methods: From 2006 to 2010 the Reinier de Graaf Hospital implanted 160 large-head Magnum M2 MoM THAs (Biomet Inc. Warsaw, Indiana, USA) in 150 patients. These patients were recalled after a warning from the Dutch Orthopaedic Association. Patients were offered a clinical and radiographic assessment of the hip prosthesis, serum control on cobalt and chromium ions, and an ultrasound of the hip. If indicated, additional MARS-MRI or CT scan was performed. Descriptive statistical analysis, correlations, t -tests, non-parametric tests and implant survival were calculated. Results: The mean follow-up was 6.1 years (4.8-8.4). A cumulative survival rate of 93.1% (95% CI: 88.3-98%) was found after 5 years. Reasons for revision were loosening, pain, infection and pseudotumour formation. The prevalence of pseudotumour formation around the prostheses was 8.75%. Conclusions: This study reports the first results of 160 MoM THAs implanted in our clinic from 2006-2010. In total, 13 (8.1%) of the THAs were eligible for revision after the recall. In most patients the reason for revision was pseudotumour formation. A total of 14 (8.75%) pseudotumours were diagnosed at the first recall. These results show that a comprehensive follow-up strategy is essential for MoM THAs to promptly identify and manage early complications.